A beginner's guide to immortality : from alchemy to avatars - Birmingham, Maria (Owlkids Books, 2015)
"Do you want to cheat death? If you said yes, then this is just the book you've been looking for-- the guide to immortality! Discover the ways people have attempted to live forever... or died trying" -- Page 4 of cover.